Preparation process of an antifouling and wear-resistant protective coating and its application in thermal paper
By applying anti-fouling and wear-resistant protective coating on thermal paper, the problem of poor image stability of thermal paper is solved, effective anti-fouling and wear-resistant protection of the surface of thermal paper is achieved, and its application performance is improved.
Patent Information
- Application Number
- CN202410925359.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-07-11
AI Technical Summary
The image stability of thermally sensitive recording paper is poor, resulting in susceptibility to contamination and wear during use, affecting the clarity, integrity and durability of the recorded information.
Using a preparation process of anti-fouling and wear-resistant protective coating, functionalized polysiloxane, polyindole coated nanosilica and styrene acrylic emulsion are prepared into top coat coating, and uniformly coated on thermal paper to cure to form an anti-fouling and wear-resistant protective coating.
It significantly improves the anti-fouling and wear resistance of thermal paper, improves its protective performance, enhances image stability, prevents pollution and wear, and improves the durability of recording information.
Smart Images

Figure BDA0004937972440000031 
Figure BDA0004937972440000101 
Figure BDA0004937972440000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a preparation process of an antifouling and wear-resistant protective coating and an application thereof in thermal paper. Background Art
[0002] As a type of information recording material, thermal recording paper has the characteristics of small and flexible printing device, single and cheap printing consumables, simple and convenient printing operation, quiet and fast printing process, fine and clear printing products, etc. It has been widely used in fax communication, medical imaging, financial bills, logistics labels and other fields. However, the poor image stability of thermal paper also has many restrictions on its application. With the continuous expansion of the application scope of thermal paper, the demand for protective thermal paper with high image stability has become increasingly strong.
[0003] Ordinary thermal paper usually refers to a paper base layer, a bottom layer and a top coating layer (thermal layer), and the color-forming components in the thermal layer are mixed in the same coating without isolation, and basically have no protective properties. This makes thermal paper susceptible to contamination and wear during use, affecting the clarity, integrity and durability of recorded information. Therefore, it is necessary to propose an anti-fouling and wear-resistant protective coating, apply it to the production and manufacturing of thermal paper, improve the anti-fouling and wear-resistant properties of thermal paper, and improve the protective properties of ordinary thermal paper. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation process of an antifouling and wear-resistant protective coating and its application in thermal paper, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A preparation process for an antifouling and wear-resistant protective coating, wherein the preparation process for the antifouling and wear-resistant protective coating comprises: performing ring-opening polymerization on functionalized cyclotetrasiloxane and trifluoropropylmethylcyclotrisiloxane and end-capping with 1,3-bis(3-aminopropyl)tetramethyldisiloxane to obtain functionalized polysiloxane; preparing a top coating by preparing styrene acrylic emulsion, polybenzazole-coated nano-silica and functionalized polysiloxane, and uniformly coating the top coating on thermal paper and curing the top coating to obtain an antifouling and wear-resistant protective coating;
[0007] The polybenzazole-coated nano-silica is prepared by oxidative polymerization of indole and indole-6-carboxylic acid and depositing them on the surface of nano-silica;
[0008] The functionalized cyclotetrasiloxane is prepared by reacting heptamethylcyclotetrasiloxane with 9,10-dihydro-9-oxa-10-allylphosphaphenanthrene-10-oxide.
[0009] As an optimization, the preparation process of the antifouling and wear-resistant protective coating includes the following preparation steps:
[0010] (1) In a nitrogen atmosphere, nano-silica, indole, indole-6-carboxylic acid, and anhydrous ethanol are mixed uniformly in a mass ratio of 1:(3-4):(1-1.4):(20-24), and ultrasonically dispersed for 1-2 hours to prepare a mixed solution; in a nitrogen atmosphere, at 0-2°C, 300-500 r / min stirring conditions, the oxidant solution is uniformly added to the mixed solution within 20 minutes, and the stirring reaction is continued for 20-24 hours, filtered, washed with anhydrous ethanol and deionized water for 3-5 times each, and dried at 60-70°C for 8-10 hours under vacuum conditions to obtain polyindole-coated nano-silica;
[0011] (2) functionalized cyclotetrasiloxane, trifluoropropylmethylcyclotrisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are mixed uniformly in a mass ratio of 1:(0.6-0.8):(0.01-0.03):(0.01-0.03), stirred at 65-75°C and 300-500r / min for 35-45min, a capping agent of 0.2-0.3 times the mass of the functionalized cyclotetrasiloxane is added, the stirring reaction is continued for 16-20min, the temperature is lowered to 40-50°C and the stirring is continued for 10-12min, after cooling to room temperature, an equal volume of deionized water and toluene are mixed and washed, the mixture is allowed to stand for stratification, the aqueous phase is removed, the washing is repeated 3-5 times, the organic phase is placed in a drying oven, and dried at 50-60°C under vacuum conditions for 8-10h to obtain a functionalized polysiloxane;
[0012] (3) Styrene acrylic emulsion with a solid content of 40-42%, polybenzazole-coated nano-silica, functionalized polysiloxane, and dicyclohexylcarbodiimide are uniformly mixed in a mass ratio of 1: (0.06-0.08): (0.05-0.07): (0.002-0.003), and stirred at 10-30° C. and 300-500 r / min for 20-30 min to prepare a top coating; the top coating is applied and cured on the surface of thermal paper, and the paper is sealed and stored away from light to obtain an anti-fouling and wear-resistant protective coating.
[0013] As an optimization, the oxidant solution in step (1) is prepared by uniformly mixing ammonium persulfate (0.06 to 0.08 times the mass of indole) and deionized water in a mass ratio of 1:(4 to 6).
[0014] As an optimization, the functionalized cyclotetrasiloxane in step (2) is prepared by adding heptamethylcyclotetrasiloxane and 9,10-dihydro-9-oxa-10-allylphosphaphenanthrene-10-oxide in a molar ratio of 1:1 to toluene with a mass of 9 to 11 times that of heptamethylcyclotetrasiloxane, adding chloroplatinic acid with a mass of 0.03 to 0.05 times that of heptamethylcyclotetrasiloxane, stirring at 70 to 80° C. and 300 to 500 r / min for reaction for 2 to 3 hours, and drying at 50 to 60° C. under vacuum conditions for 8 to 10 hours to obtain the functionalized cyclotetrasiloxane.
[0015] As an optimization, the reaction process of the functionalized cyclotetrasiloxane is:
[0016]
[0017] As an optimization, the capping agent in step (2) is 1,3-bis(3-aminopropyl)tetramethyldisiloxane.
[0018] As an optimization, the process parameters of the coating and curing in step (3) are: the top coating is evenly coated on the surface of the thermal paper by a coating machine using a wire rod coating method, and the coating amount is controlled at 4 to 5 g / m 2 , under vacuum conditions, dry at 50-60°C for 6-7 hours, and balance at a relative humidity of 50-52% and a temperature of 22-24°C for 8-10 hours.
[0019] As an optimization, the thermal paper in step (3) was purchased from Guangzhou Baixin Paper Co., Ltd.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] When preparing the antifouling and wear-resistant protective coating, the present invention comprises the following steps: oxidatively polymerizing indole and indole-6-carboxylic acid, and depositing them on the surface of nano-silica to obtain polyindole-coated nano-silica; reacting heptamethylcyclotetrasiloxane with 9,10-dihydro-9-oxa-10-allylphosphaphenanthrene-10-oxide to obtain functionalized cyclotetrasiloxane; ring-opening polymerization of functionalized cyclotetrasiloxane and trifluoropropylmethylcyclotrisiloxane, and end-capping with 1,3-bis(3-aminopropyl)tetramethyldisiloxane to obtain functionalized polysiloxane; and preparing a top coating by mixing styrene-acrylic emulsion, polyindole-coated nano-silica, and functionalized polysiloxane, and uniformly coating the top coating on thermal paper and curing the top coating to obtain the antifouling and wear-resistant protective coating.
[0022] Firstly, indole and indole-6-carboxylic acid are oxidatively polymerized and deposited on the surface of nano-silica to prepare polybendole-coated nano-silica, and carboxyl groups are introduced into the polybendole-coated nano-silica; a large amount of static electricity is easily accumulated on the surface of thermal paper, which affects the inkjet coverage during printing and easily causes the phenomenon of poor printing quality, so it is necessary to solve the problem of static electricity accumulation on the surface of thermal paper, polybendole is a conductive polymer, which can form a conductive path in the matrix resin, and give the antifouling and wear-resistant protective coating excellent antistatic performance; nano-silica is an inorganic rigid nano-particle, which is dispersed in the antifouling and wear-resistant protective coating as a reinforcing filler, and can give the antifouling and wear-resistant protective coating excellent wear resistance.
[0023] Secondly, the Si-H bond on the heptamethylcyclotetrasiloxane is subjected to a hydrosilylation reaction with the carbon-carbon double bond on the 9,10-dihydro-9-oxa-10-allylphosphaphenanthrene-10-oxide to obtain a functionalized cyclotetrasiloxane, and a DOPO structure is introduced into the functionalized cyclotetrasiloxane; the functionalized cyclotetrasiloxane and trifluoropropylmethylcyclotrisiloxane are subjected to ring-opening polymerization, and the functionalized polysiloxane is capped with 1,3-bis(3-aminopropyl)tetramethyldisiloxane to obtain a functionalized polysiloxane, and a DOPO structure and a CF bond are introduced into the side chain of the functionalized polysiloxane, and amino groups are introduced into both ends of the main chain of the functionalized polysiloxane; the DOPO structure has a biphenyl ring and a phenanthrene ring structure in its molecular structure, especially the side phosphorus group is introduced in the form of a cyclic O=PO bond, so it has higher thermal stability and chemical stability than general, non-cyclic organic phosphates, better flame retardancy, and imparts antifouling and wear resistance. The protective coating has excellent flame retardant properties; the bond energy of the CF bond is relatively high and the polarizability is relatively low. The matrix material containing the CF bond has a high repellency not only to aqueous substances, but also to oily substances, which can give the antifouling and wear-resistant protective coating excellent antifouling properties and protect the surface of the thermal paper from being polluted; the Si-O bond has high heat resistance and chemical stability and can form a carbon layer during combustion, which plays a role in heat insulation, oxygen isolation, and combustion inhibition, further improving the flame retardant properties of the antifouling and wear-resistant protective coating; the amino groups introduced at both ends of the main chain of the functionalized polysiloxane can undergo amidation reaction with the carboxyl groups introduced on the polyindole-coated nano-silica and the carboxyl groups on the styrene-acrylic emulsion molecular chain to form a cross-linked network, cross-link and cure, and inhibit the relative slip between the molecular chains, further improving the wear resistance of the antifouling and wear-resistant protective coating and protecting the surface of the thermal paper from being worn. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1
[0026] A preparation process of an antifouling and wear-resistant protective coating, the preparation process of the antifouling and wear-resistant protective coating comprising the following preparation steps:
[0027] (1) In a nitrogen atmosphere, nano-silica, indole, indole-6-carboxylic acid, and anhydrous ethanol were mixed in a mass ratio of 1:3:1:20, and ultrasonically dispersed for 1 hour to prepare a mixed solution; ammonium persulfate (0.06 times the mass of indole) and deionized water were mixed in a mass ratio of 1:4 to prepare an oxidant solution; in a nitrogen atmosphere, at 0°C, 300 r / min stirring conditions, the oxidant solution was uniformly added dropwise to the mixed solution within 20 minutes, and the stirring reaction was continued for 20 hours, filtered, washed with anhydrous ethanol and deionized water 3 times each, and dried at 60°C for 10 hours under vacuum conditions to obtain polyindole-coated nano-silica;
[0028] (2) adding heptamethylcyclotetrasiloxane and 9,10-dihydro-9-oxa-10-allylphosphaphenanthrene-10-oxide in a molar ratio of 1:1 to toluene with a mass of 9 times that of heptamethylcyclotetrasiloxane, adding chloroplatinic acid with a mass of 0.03 times that of heptamethylcyclotetrasiloxane, stirring at 70°C and 300 r / min for 3 h, and drying at 50°C for 10 h under vacuum conditions to obtain functionalized cyclotetrasiloxane; adding functionalized cyclotetrasiloxane, trifluoropropylmethylcyclotrisiloxane, tetramethylammonium hydroxide, and dimethyl sulfoxide in a mass ratio of 1:0 .6:0.01:0.01 were mixed evenly, stirred at 65°C and 300r / min for 45min, 1,3-bis(3-aminopropyl)tetramethyldisiloxane (0.2 times the mass of functionalized cyclotetrasiloxane) was added, and the reaction was continued with stirring for 20min, the temperature was lowered to 40°C and stirring was continued for 12min, and after cooling to room temperature, an equal volume of deionized water and toluene were mixed and washed, and the layers were allowed to stand and the aqueous phase was removed. The washing was repeated 3 times, and the organic phase was placed in a drying oven and dried at 50°C for 10h under vacuum conditions to obtain functionalized polysiloxane;
[0029] (3) Styrene acrylic emulsion with a solid content of 40%, polybenzazole-coated nano-silica, functionalized polysiloxane, and dicyclohexylcarbodiimide were mixed uniformly in a mass ratio of 1:0.06:0.05:0.002, and stirred at 10°C and 300 r / min for 30 min to prepare a top coating; the top coating was evenly coated on the surface of the thermal paper using a wire rod coating machine, and the coating amount was controlled at 4 g / m 2 , dried at 50°C for 7 hours under vacuum conditions, balanced at a relative humidity of 50% and a temperature of 22°C for 10 hours, and stored in a sealed container away from light to obtain an anti-fouling and wear-resistant protective coating.
[0030] Example 2
[0031] A preparation process of an antifouling and wear-resistant protective coating, the preparation process of the antifouling and wear-resistant protective coating comprising the following preparation steps:
[0032] (1) In a nitrogen atmosphere, nano-silica, indole, indole-6-carboxylic acid, and anhydrous ethanol were mixed in a mass ratio of 1:3.5:1.2:22, and ultrasonically dispersed for 1.5 hours to prepare a mixed solution; ammonium persulfate (0.07 times the mass of indole) and deionized water were mixed in a mass ratio of 1:5 to prepare an oxidant solution; in a nitrogen atmosphere, at 1°C, 400 r / min stirring conditions, the oxidant solution was uniformly added dropwise to the mixed solution within 20 minutes, and the stirring reaction was continued for 22 hours, filtered, washed with anhydrous ethanol and deionized water 4 times each, and dried at 65°C under vacuum conditions for 9 hours to obtain polyindole-coated nano-silica;
[0033] (2) adding heptamethylcyclotetrasiloxane and 9,10-dihydro-9-oxa-10-allylphosphaphenanthrene-10-oxide in a molar ratio of 1:1 to toluene with a mass of 10 times that of heptamethylcyclotetrasiloxane, adding chloroplatinic acid with a mass of 0.04 times that of heptamethylcyclotetrasiloxane, stirring at 75°C and 400 r / min for 2.5 h, and drying at 55°C for 9 h under vacuum conditions to obtain functionalized cyclotetrasiloxane; adding functionalized cyclotetrasiloxane, trifluoropropylmethylcyclotrisiloxane, tetramethylammonium hydroxide, and dimethyl sulfoxide in a mass ratio of 1:1. 0.7:0.02:0.02 were mixed evenly, stirred at 70°C and 400r / min for 40min, 1,3-bis(3-aminopropyl)tetramethyldisiloxane (0.25 times the mass of functionalized cyclotetrasiloxane) was added, and the reaction was continued with stirring for 18min, the temperature was lowered to 45°C and the stirring was continued for 11min, and after cooling to room temperature, an equal volume of deionized water and toluene were mixed and washed, and the layers were allowed to stand and the aqueous phase was removed. The washing was repeated 4 times, and the organic phase was placed in a drying oven and dried at 55°C for 9h under vacuum conditions to obtain functionalized polysiloxane;
[0034] (3) Styrene acrylic emulsion with a solid content of 41%, polybenzazole-coated nano-silica, functionalized polysiloxane, and dicyclohexylcarbodiimide were mixed uniformly in a mass ratio of 1:0.07:0.06:0.0025, and stirred at 20° C. and 400 r / min for 25 min to prepare a top coating; the top coating was evenly coated on the surface of the thermal paper using a coating machine using a wire rod coating method, and the coating amount was controlled at 4.5 g / m 2 , dried at 55°C for 6.5h under vacuum conditions, balanced at a relative humidity of 51% and a temperature of 23°C for 9h, and stored in a sealed container away from light to obtain an antifouling and wear-resistant protective coating.
[0035] Example 3
[0036] A preparation process of an antifouling and wear-resistant protective coating, the preparation process of the antifouling and wear-resistant protective coating comprising the following preparation steps:
[0037] (1) In a nitrogen atmosphere, nano-silica, indole, indole-6-carboxylic acid, and anhydrous ethanol were mixed in a mass ratio of 1:4:1.4:24, and ultrasonically dispersed for 2 hours to prepare a mixed solution; ammonium persulfate (0.08 times the mass of indole) and deionized water were mixed in a mass ratio of 1:6 to prepare an oxidant solution; in a nitrogen atmosphere, at 2°C, 500 r / min stirring conditions, the oxidant solution was uniformly added dropwise to the mixed solution within 20 minutes, and the stirring reaction was continued for 20 hours, filtered, washed with anhydrous ethanol and deionized water 5 times each, and dried at 70°C under vacuum conditions for 8 hours to obtain polyindole-coated nano-silica;
[0038] (2) adding heptamethylcyclotetrasiloxane and 9,10-dihydro-9-oxa-10-allylphosphaphenanthrene-10-oxide in a molar ratio of 1:1 to toluene with a mass of 11 times that of heptamethylcyclotetrasiloxane, adding chloroplatinic acid with a mass of 0.05 times that of heptamethylcyclotetrasiloxane, stirring at 80°C and 500 r / min for 2 h, and drying at 60°C for 8 h under vacuum conditions to obtain functionalized cyclotetrasiloxane; adding functionalized cyclotetrasiloxane, trifluoropropylmethylcyclotrisiloxane, tetramethylammonium hydroxide, and dimethyl sulfoxide in a mass ratio of 1:1. 0.8:0.03:0.03 were mixed evenly, stirred at 75°C and 500r / min for 35min, 1,3-bis(3-aminopropyl)tetramethyldisiloxane (0.3 times the mass of functionalized cyclotetrasiloxane) was added, and the reaction was continued with stirring for 16min, the temperature was lowered to 50°C and the stirring was continued for 10min, and after cooling to room temperature, an equal volume of deionized water and toluene were mixed and washed, and the layers were allowed to stand and the aqueous phase was removed. The washing was repeated 5 times, and the organic phase was placed in a drying oven and dried at 60°C for 8h under vacuum conditions to obtain functionalized polysiloxane;
[0039] (3) Styrene acrylic emulsion with a solid content of 42%, polybenzazole-coated nano-silica, functionalized polysiloxane, and dicyclohexylcarbodiimide were mixed uniformly in a mass ratio of 1:0.08:0.07:0.003, stirred at 30°C and 500 r / min for 20 min to prepare a top coating; the top coating was evenly coated on the surface of the thermal paper using a wire rod coating machine, and the coating amount was controlled at 5 g / m 2 , dried at 60°C for 6 hours under vacuum conditions, balanced at a relative humidity of 52% and a temperature of 24°C for 8 hours, and stored in a sealed container away from light to obtain an anti-fouling and wear-resistant protective coating.
[0040] Comparative Example 1
[0041] The difference between the preparation method of the antifouling and wear-resistant protective coating of Comparative Example 1 and Example 2 is that step (1) is not performed, and step (3) is modified as follows: a styrene-acrylic emulsion with a solid content of 41%, a functionalized polysiloxane, and dicyclohexylcarbodiimide are mixed uniformly in a mass ratio of 1:0.06:0.0025, and stirred at 20°C and 400r / min for 25min to prepare a top coating; the top coating is evenly coated on the surface of the thermal paper by a coating machine using a wire rod coating method, and the coating amount is controlled at 4.5g / m 2 , dried at 55°C for 6.5 hours under vacuum conditions, balanced at a relative humidity of 51% and a temperature of 23°C for 9 hours, sealed and stored away from light to obtain an antifouling and wear-resistant protective coating. The remaining steps are the same as in Example 2.
[0042] Comparative Example 2
[0043] The difference between the preparation method of the antifouling and wear-resistant protective coating of Comparative Example 2 and Example 2 lies in the difference in step (2), and step (2) is modified as follows: octamethylcyclotetrasiloxane, trifluoropropylmethylcyclotrisiloxane, tetramethylammonium hydroxide, and dimethyl sulfoxide are mixed uniformly in a mass ratio of 1:0.7:0.02:0.02, stirred at 70°C and 400r / min for 40min, 1,3-bis(3-aminopropyl)tetramethyldisiloxane with a mass of 0.25 times that of octamethylcyclotetrasiloxane is added, and the stirring reaction is continued for 18min, the temperature is lowered to 45°C and the stirring is continued for 11min, and after cooling to room temperature, an equal volume of deionized water and toluene are mixed and washed, the mixture is allowed to stand for stratification, the aqueous phase is removed, the washing is repeated 4 times, the organic phase is placed in a drying oven, and dried at 55°C for 9h under vacuum conditions to obtain a functionalized polysiloxane. The remaining steps are the same as those of Example 2.
[0044] Comparative Example 3
[0045] The preparation method of the antifouling and wear-resistant protective coating of Comparative Example 3 is different from that of Example 2 only in step (2). Step (2) is modified as follows: heptamethylcyclotetrasiloxane and 9,10-dihydro-9-oxa-10-allylphosphaphenanthrene-10-oxide are added in a molar ratio of 1:1 to toluene with a mass of 10 times that of heptamethylcyclotetrasiloxane, and 0.04 times the mass of heptamethylcyclotetrasiloxane is added with chloroplatinic acid, and the mixture is stirred at 75°C and 400 r / min for 2.5 h, and dried at 55°C for 9 h under vacuum to obtain functionalized cyclotetrasiloxane; functionalized cyclotetrasiloxane and octamethylcyclotetrasiloxane are added. , tetramethylammonium hydroxide, and dimethyl sulfoxide were mixed uniformly in a mass ratio of 1:0.7:0.02:0.02, stirred at 70°C and 400r / min for 40min, 1,3-bis(3-aminopropyl)tetramethyldisiloxane (0.25 times the mass of the functionalized cyclotetrasiloxane) was added, and the reaction was continued for 18min, the temperature was cooled to 45°C and stirred for 11min, and after cooling to room temperature, an equal volume of deionized water and toluene were mixed and washed, and the layers were allowed to stand, and the aqueous phase was removed. The washing was repeated 4 times, and the organic phase was placed in a drying oven, and dried at 55°C for 9h under vacuum conditions to obtain a functionalized polysiloxane. The remaining steps were the same as those in Example 2.
[0046] Comparative Example 4
[0047] The difference between the preparation method of the antifouling and wear-resistant protective coating of Comparative Example 4 and Example 2 is that step (2) is not performed, and step (3) is modified as follows: a styrene-acrylic emulsion with a solid content of 41%, polybenzazole-coated nano-silica, and dicyclohexylcarbodiimide are mixed uniformly in a mass ratio of 1:0.07:0.0025, stirred at 20°C and 400r / min for 25min, and prepared into a top coating; the top coating is evenly coated on the surface of the thermal paper by a coating machine using a wire rod coating method, and the coating amount is controlled at 4.5g / m 2 , dried at 55°C for 6.5 hours under vacuum conditions, balanced at a relative humidity of 51% and a temperature of 23°C for 9 hours, sealed and stored away from light to obtain an antifouling and wear-resistant protective coating. The remaining steps are the same as in Example 2.
[0048] Test Example 1
[0049] Antistatic performance test
[0050] Test method: The surface resistance of the embodiment and the comparative example was measured with a surface resistance tester, and the surface resistivity was calculated, and the surface resistivity was used to characterize the antistatic performance of the embodiment and the comparative example. The results are shown in Table 1.
[0051] Table 1
[0052] Surface resistivity(Ω) Surface resistivity(Ω) Example 1 <![CDATA[6.6×10 7 ]]> Comparative Example 1 <![CDATA[2.6×10 11 ]]> Example 2 <![CDATA[5.6×10 7 ]]> Comparative Example 2 <![CDATA[8.5×10 7 ]]> Example 3 <![CDATA[6.8×10 7 ]]> Comparative Example 3 <![CDATA[9.4×10 7 ]]> Comparative Example 4 <![CDATA[8.8×10 7 ]]>
[0053] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the antifouling and wear-resistant protective coating prepared by the present invention has good antistatic performance.
[0054] By comparison, the surface resistivity of Examples 1 to 3 is less than that of Comparative Example 1, indicating that indole and indole-6-carboxylic acid are oxidatively polymerized and deposited on the surface of nano-silica to prepare polybenzole-coated nano-silica; a large amount of static electricity is easily accumulated on the surface of thermal paper, which affects inkjet coverage during printing and easily causes poor printing quality. Therefore, the problem of static electricity accumulation on the surface of thermal paper needs to be solved. Polybenzole is a conductive polymer that can form a conductive path in the matrix resin, giving the anti-fouling and wear-resistant protective coating excellent anti-static properties.
[0055] Test Example 2
[0056] Flame retardant performance test
[0057] Test method: pour the top coating prepared in the embodiment and the comparative example into a polytetrafluoroethylene mold, keep it at 55°C for 7 hours, demould it after cooling to room temperature, prepare it into a standard specimen according to GB / T5454, and test the limiting oxygen index of the standard specimen according to GB / T5454. The results are shown in Table 2.
[0058] Table 2
[0059] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 30.85 Comparative Example 1 29.87 Example 2 31.26 Comparative Example 2 25.17 Example 3 31.07 Comparative Example 3 29.63 Comparative Example 4 21.46
[0060] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the antifouling and wear-resistant protective coating prepared by the present invention has good flame retardant properties.
[0061] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Examples 2 and 4, indicating that the Si-H bond on heptamethylcyclotetrasiloxane and the carbon-carbon double bond on 9,10-dihydro-9-oxa-10-allylphosphaphenanthrene-10-oxide are subjected to a hydrosilylation reaction to obtain a functionalized cyclotetrasiloxane, and a DOPO structure is introduced into the functionalized cyclotetrasiloxane; the functionalized cyclotetrasiloxane and trifluoropropylmethylcyclotrisiloxane are ring-opened polymerized and end-capped with 1,3-bis(3-aminopropyl)tetramethyldisiloxane to obtain a functionalized polysiloxane. Oxane, introduces DOPO structure on the side chain of functionalized polysiloxane; DOPO structure contains biphenyl ring and phenanthrene ring structure in its molecular structure, especially the side phosphorus group is introduced in the form of cyclic O=PO bond, which has higher thermal stability and chemical stability than general, non-annulated organic phosphates, and better flame retardant performance, thus giving the antifouling and wear-resistant protective coating excellent flame retardant performance; Si-O bond has high heat resistance and chemical stability, and can form a carbon layer during combustion, which plays a role in heat insulation, oxygen isolation, and combustion inhibition, further improving the flame retardant performance of the antifouling and wear-resistant protective coating.
[0062] Test Example 3
[0063] Antifouling performance test
[0064] Test method: The water drop contact angles of the embodiments and comparative examples were tested using the sessile drop method on an OCA20 contact angle meter, with the water drop volume being 5 μL. The results are shown in Table 3.
[0065] Table 3
[0066]
[0067]
[0068] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the antifouling and wear-resistant protective coating prepared by the present invention has good antifouling performance.
[0069] By comparison, the contact angles of Examples 1 to 3 are greater than the contact angle of Comparative Example 3, indicating that the functionalized cyclotetrasiloxane and trifluoropropylmethylcyclotrisiloxane are ring-opening polymerized and end-capped with 1,3-bis(3-aminopropyl)tetramethyldisiloxane to obtain a functionalized polysiloxane, and a CF bond is introduced into the side chain of the functionalized polysiloxane; the CF bond has a higher bond energy and a lower polarizability, and the matrix material containing the CF bond has a higher repellency not only to aqueous substances, but also to oily substances, and can give the antifouling and wear-resistant protective coating excellent antifouling properties, protecting the surface of the thermal paper from contamination.
[0070] Test Example 4
[0071] Wear resistance test
[0072] Test method: The wear resistance of the embodiment and the comparative example was tested using a MS-T3001 friction tester. The conditions for the wear test were set as follows: rotation speed 300r / min, load 5N, test duration 30min, and rotation radius 3mm. The steel ball used for friction was made of GCr15 bearing steel with a diameter of 4mm. The surface wear scar width and surface wear scar depth of the embodiment and the comparative example were measured using a Zeiss ObserverZ1m metallographic microscope. The wear rate was calculated. The results are shown in Table 4.
[0073] Table 4
[0074]
[0075]
[0076] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 4, it can be found that the antifouling and wear-resistant protective coating prepared by the present invention has good wear resistance.
[0077] By comparison, the wear rates of Examples 1 to 3 are less than those of Comparative Examples 1 and 4, indicating that indole and indole-6-carboxylic acid are oxidatively polymerized and deposited on the surface of nano-silica to prepare polyindole-coated nano-silica, and carboxyl groups are introduced into the polyindole-coated nano-silica; functionalized cyclotetrasiloxane and trifluoropropylmethylcyclotrisiloxane are ring-opened polymerized and end-capped with 1,3-bis(3-aminopropyl)tetramethyldisiloxane to prepare functionalized polysiloxane, and amino groups are introduced into both ends of the main chain of the functionalized polysiloxane. The amino groups introduced at both ends of the main chain of the functionalized polysiloxane can undergo amidation reaction with the carboxyl groups introduced on the polyindole-coated nano-silica and the carboxyl groups on the styrene-acrylic emulsion molecular chains to form a cross-linked network, cross-linking and curing, thereby inhibiting the relative slip between the molecular chains and improving the wear resistance of the anti-fouling and wear-resistant protective coating. Nano-silica is an inorganic rigid nanoparticle. It is dispersed in the anti-fouling and wear-resistant protective coating as a reinforcing filler, which can give the anti-fouling and wear-resistant protective coating excellent wear resistance and protect the surface of the thermal paper from wear.
[0078] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A process for preparing an antifouling and wear-resistant protective coating, characterized in that: The preparation process of the antifouling and wear-resistant protective coating comprises the following preparation steps: (1) In a nitrogen atmosphere, nano-silica, indole, indole-6-carboxylic acid, and anhydrous ethanol are mixed uniformly in a mass ratio of 1:(3-4):(1-1.4):(20-24), and ultrasonically dispersed for 1-2 hours to prepare a mixed solution; in a nitrogen atmosphere, at 0-2°C, 300-500 r / min stirring conditions, the oxidant solution is uniformly added dropwise to the mixed solution within 20 minutes, the stirring reaction is continued for 20-24 hours, the mixture is filtered, washed with anhydrous ethanol and deionized water for 3-5 times each, and dried at 60-70°C for 8-10 hours under vacuum conditions to obtain polyindole-coated nano-silica; (2) functionalized cyclotetrasiloxane, trifluoropropylmethylcyclotrisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are mixed uniformly in a mass ratio of 1:(0.6-0.8):(0.01-0.03):(0.01-0.03), stirred at 65-75°C and 300-500r / min for 35-45min, a capping agent of 0.2-0.3 times the mass of the functionalized cyclotetrasiloxane is added, the stirring reaction is continued for 16-20min, the temperature is lowered to 40-50°C and the stirring is continued for 10-12min, after cooling to room temperature, an equal volume of deionized water and toluene are mixed and washed, the mixture is allowed to stand for stratification, the aqueous phase is removed, the washing is repeated 3-5 times, the organic phase is placed in a drying oven, and dried at 50-60°C under vacuum conditions for 8-10h to obtain a functionalized polysiloxane; (3) Styrene acrylic emulsion with a solid content of 40-42%, polybenzazole-coated nano-silica, functionalized polysiloxane, and dicyclohexylcarbodiimide are uniformly mixed in a mass ratio of 1: (0.06-0.08): (0.05-0.07): (0.002-0.003), and stirred at 10-30° C. and 300-500 r / min for 20-30 min to prepare a top coating; the top coating is applied and cured on the surface of thermal paper, and the paper is sealed and stored away from light to obtain an anti-fouling and wear-resistant protective coating.
2. The process for preparing an antifouling and wear-resistant protective coating according to claim 1, characterized in that: The oxidant solution in step (1) is prepared by uniformly mixing ammonium persulfate (0.06 to 0.08 times the mass of indole) and deionized water in a mass ratio of 1:(4 to 6).
3. The process for preparing an antifouling and wear-resistant protective coating according to claim 1, characterized in that: The functionalized cyclotetrasiloxane in step (2) is prepared by adding heptamethylcyclotetrasiloxane and 9,10-dihydro-9-oxa-10-allylphosphaphenanthrene-10-oxide in a molar ratio of 1:1 to toluene with a mass of 9 to 11 times that of heptamethylcyclotetrasiloxane, adding chloroplatinic acid with a mass of 0.03 to 0.05 times that of heptamethylcyclotetrasiloxane, stirring at 70 to 80° C. and 300 to 500 r / min for reaction for 2 to 3 hours, and drying at 50 to 60° C. under vacuum conditions for 8 to 10 hours to obtain the functionalized cyclotetrasiloxane.
4. The process for preparing an antifouling and wear-resistant protective coating according to claim 1, characterized in that: The reaction process of the functionalized cyclotetrasiloxane is:
5. The process for preparing an antifouling and wear-resistant protective coating according to claim 1, characterized in that: The capping agent in step (2) is 1,3-bis(3-aminopropyl)tetramethyldisiloxane.
6. The process for preparing an antifouling and wear-resistant protective coating according to claim 1, characterized in that: The process parameters of the coating and curing in step (3) are as follows: the top coating is evenly coated on the surface of the thermal paper by a coating machine using a wire rod coating method, and the coating amount is controlled at 4 to 5 g / m 2 , under vacuum conditions, dry at 50-60°C for 6-7 hours, and balance at a relative humidity of 50-52% and a temperature of 22-24°C for 8-10 hours.
7. Use of the antifouling and wear-resistant protective coating prepared by the preparation process of the antifouling and wear-resistant protective coating according to any one of claims 1 to 6 in thermal paper.
Citation Information
Patent Citations
Wear-resistant composite conductive coating and preparation method thereof
CN110885581A
Thermosensitive engineering drawing and preparation method thereof
CN114687244A
Resin composition for hard coating hanving antiblocking and antistatic property and hard coating film using the same
KR101321414B1